CrO3 supported on sargassum-based activated carbon as low temperature catalysts for the selective catalytic reduction of NO with NH3. (1st March 2017) - Li, Sujing; Wang, Xiaoxiang; Tan, Shan; Shi, Yun; Li, Wei
Abstract: Sargassum based activated carbon (SAC) doped with various transition metals was developed via impregnation as a new catalyst for selective catalytic reduction of NO with NH3 (NH3 -SCR) in the temperature range of 50–250 °C with gas hourly space velocity (GHSV) of 80, 000 h −1 . The samples were characterized by means of Brunauer–Emmett–Teller method (BET), scanning electron microscope (SEM), NH3 temperature-programmed desorption (NH3 -TPD), H2 temperature-programmed reduction (H2 -TPR), and X-ray photoelectron spectroscopy (XPS). The impacts of water (H2 O) and sulfur dioxide (SO2 ) on the SCR activity of the CrO3 /SAC catalyst were also discussed. The experimental results showed that the introduction of Cr increased the acid sites formed on the surface of catalysts and enhanced the SCR reaction rate by the valence changing between Cr 6+ and its lower oxidized states (Cr 5+, Cr 3+ and Cr 2+ ). The catalyst with a Cr/SAC mass ratio of 2%:1 exhibited the best NOx -removing performance, with NOx conversion greater than 90% at the temperature of 125–150 °C. Moreover, it had excellent water and sulfur tolerance, making the Cr-doped SAC catalyst as a good candidate for reducing the NOx emission from fired power plants.